Quality of life and risk behaviors for eating disorders in university students (Revista Contexto & Saúde, 2025)
Eating disorders can lead to numerous health impairments, including poor quality of life. This study aimed to explore the association between quality of life and risk behaviors for eating disorders. A cross-sectional study was conducted with a sample of 353 health sciences university students from southern Brazil. Quality of life was assessed using the WHOQOL-BREF, while risk behaviors for eating disorders were evaluated through the EAT-26. Data analysis included descriptive statistics, non-parametric tests, and Poisson regression. The mean age of the sample was 25.9 ± 8.2 years, with a median (Med) total quality of life score of 66.3 points (interquartile range [IQR]: 58.6–74.0), and a prevalence of poor quality of life of 28.3% (95% Confidence Interval [CI]: 23.6–33.0). A lower quality of life score was observed among students with risk behaviors (Med: 63.0; IQR: 52.9–70.2) compared to those without risk behaviors (Med: 67.3; IQR: 60.6–75.0; p=0.002). After adjustment, university students with risk behaviors for eating disorders had a 79% higher probability of experiencing poor quality of life (Prevalence Ratio [PR] = 1.79; 95% CI: 1.28–2.50; p=0.001) compared to those without risk behaviors. Thus, the findings of this study indicate a poorer quality of life among university students with risk behaviors for eating disorders.
Keywords: quality of life; eating disorders; university students